2003
DOI: 10.1210/jc.2002-020787
|View full text |Cite
|
Sign up to set email alerts
|

A New Nonisotopic, Highly Sensitive Assay for the Measurement of Human Placental Growth Hormone: Development and Clinical Implications

Abstract: Human placental GH (hGH-V) is a variant of pituitary hGH (hGH-N) synthesized and secreted by syncytiotrophoblasts during pregnancy. It differs from hGH-V by only 13 amino acid residues, which makes difficult a specific measurement of hGH-V without interference from hGH-N. To overcome the analytical difficulties, we produced new high affinity monoclonal antibodies specific for hGH-V. Precise screening and epitope mapping allowed identification of a pair of monoclonal antibodies suitable to establish a highly se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 31 publications
2
52
0
4
Order By: Relevance
“…Birth weight z-scores and BMI were comparable; hence no obvious explanation for the lower PGH levels in early labour was found. In a recent paper, one woman delivering vaginally was observed to have decreasing values of serum PGH shortly before delivery (9), and Wu et al found no explicit decline in PGH values up to 30 min before parturition in two patients (6). The present findings thus resemble these latter observations, as no significant changes in serum PGH values were observed during the course of vaginal delivery.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Birth weight z-scores and BMI were comparable; hence no obvious explanation for the lower PGH levels in early labour was found. In a recent paper, one woman delivering vaginally was observed to have decreasing values of serum PGH shortly before delivery (9), and Wu et al found no explicit decline in PGH values up to 30 min before parturition in two patients (6). The present findings thus resemble these latter observations, as no significant changes in serum PGH values were observed during the course of vaginal delivery.…”
Section: Discussionsupporting
confidence: 80%
“…It is controversial whether PGH levels decline in the last weeks of pregnancy. In recent studies, no significant decrease was observed (6,8,9); however, the most recent study reported decreasing values from week 37 onwards, which was most pronounced in the group of mothers carrying the smallest fetuses (3). In addition, serum PGH levels have been reported to decline during labour (4,9).…”
Section: Introductionmentioning
confidence: 95%
“…Concentrations of IGF-I and hPGH in maternal serum are tightly correlated in the second half of human pregnancy [39]. Therefore, hPGH acts as an agonist of maternal GHRs.…”
Section: Primatesmentioning
confidence: 99%
“…Es unterscheidet sich vom hypophys ä ren GH nur durch wenige Aminos ä uren, so dass es in den meisten GH-Assays kreuzreagiert. Eine spezifi sche Messung des plazentaren Wachstumshormons ist nur mit speziellen Assays m ö glich [5] . Die physiologische Bedeutung dieser plazentaren GH-Sekretion, die bislang nur beim Menschen nachgewiesen wurde, ist unklar.…”
unclassified